2018
DOI: 10.1186/s12874-018-0588-5
|View full text |Cite
|
Sign up to set email alerts
|

Putting family into family-based obesity prevention: enhancing participant engagement through a novel integrated knowledge translation strategy

Abstract: BackgroundWith 1 in 4 Canadian preschoolers considered overweight or obese, identifying risk factors for excess weight gain and developing effective interventions aimed at promoting healthy weights and related behaviours among young children have become key public health priorities. Despite the need for this research, engaging and maintaining participation is a critical challenge for long-term, family-based studies. The aim of this study is to describe the implementation and evaluation of a parent-only advisor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Unfortunately, some of these materials are mandatory information from medical ethical committees, and can therefore not be modified. Still, future recruitment strategies should balance the required information provision with participant needs, for instance, by using tailored communication and pictures [ 19 ] or by engaging parents in research development [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, some of these materials are mandatory information from medical ethical committees, and can therefore not be modified. Still, future recruitment strategies should balance the required information provision with participant needs, for instance, by using tailored communication and pictures [ 19 ] or by engaging parents in research development [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The work environment plays a critical role in fostering trusting and collaborative relationships among inter‐professional teams 34 . Honesty and trust were seen as key to building team relationships in this study, as well as earlier studies on youth engagement, 35 family engagement 3 and service user engagement 27,36 . Although prior research reported mistrust as a barrier, 27 participants in our study focussed on trust as a strength.…”
Section: Discussionmentioning
confidence: 65%
“…Few studies have examined the perceptions of engagement by broad project teams, particularly relating to youth mental health. The powerful and impactful nature of youth and family engagement has been found previously 3,11,13,44 . Happell et al, 11 for instance, found that engagement brought value and improvement to mental health research.…”
Section: Discussionmentioning
confidence: 87%
“…This study used an iterative co-design process among academics, practitioners, and other stakeholders, which evolves to the Embedded Research Translation (ERT) model † , co-developed by USAID and LASER PULSE consortium, where research is intentionally applied to a development challenge. It has similar characteristics to Integrated Knowledge Translation (IKT), which is also a collaborative research approach involving health practitioners as equal partners alongside researchers, with the goal of creating more relevant and useful solutions that result in better research outcomes [32,33,34,35]. The key principle of both ERT and IKT is involving practitioners throughout the research process starting with identification of the research question, and are actively engaged in the governance, priority setting and conduct of the research [32].…”
Section: Step 2: Understanding Issues Facing Health Practitioners In mentioning
confidence: 99%